Restructuring and Transformation of Arab Educational Institutions into Fourth-Generation Universities (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Over the years, technological development has transformed the role of universities in society andresulted in many changes in university education. New educational techniques are being shaped by theconstantly changing personal characteristics from generation to generation. This study aims to understand the transformation of existing universities to fourth-generation universities in the Arab states. The study present a literature review of the technological advancements in education and the characteristics of fourth-generation universities, which are viewed as dynamic universities that interact with the surrounding environment through four mehanacims namely, knowledge transfer, knowledge creation, knowledge application and Leaders of change in the local and international environment. The study designed a survey form and distributed it to 463 faculty members at Arab universities, analysing 400 valid forms. The findings revealed the requirements of fourth-generation Arab universities. However, these findings need to be further developed and improved. The study also revealed the variables required for the transformation of Arab universities to the fourth-generation, asan independent variable that supports the competitive position of the universities from the faculty perspective.